2017
DOI: 10.4103/ijph.ijph_236_17
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use among young adolescents in Myanmar: Findings from global youth tobacco survey

Abstract: Myanmar has higher prevalence of tobacco use among students, especially among boys. The study provides evidence-based information for developing comprehensive tobacco control programs - both education and policy interventions to reduce smoking rate among young people in Myanmar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One study showed that youth (15–24 years) in Thailand were more likely than adults (≥25 years) to notice tobacco promotions in retail stores 66 . Research also identified that school boys (47.3%) were more likely than school girls (37.0%) to notice POS advertisements or promotions in Myanmar 76 . Two studies investigated the impact of POS advertisements or promotions on youth smoking attitudes and behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that youth (15–24 years) in Thailand were more likely than adults (≥25 years) to notice tobacco promotions in retail stores 66 . Research also identified that school boys (47.3%) were more likely than school girls (37.0%) to notice POS advertisements or promotions in Myanmar 76 . Two studies investigated the impact of POS advertisements or promotions on youth smoking attitudes and behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…17 Likewise in Myanmar among students aged 13-15 years, with 13.6% of students currently using tobacco; 26.3% were among males and 3.7% among females. 18 The age of 13-15 years is vulnerable as adolescents are very easily influenced by the environment, such as peers. 19,20 Peers especially have a significant role in students because students spend more time with their peers, both at school and outside of school.…”
Section: Discussionmentioning
confidence: 99%
“…More than four of five students (83.4%) saw someone using tobacco on television, videos, or movies, and 42.3% paid attention to tobacco advertisements at the point of sale. 18 Ease of access to cigarettes for teenagers/students is also a motivating factor for smoking. Students in Southeast Asia Region reported buying cigarettes at shops/vendors in single sticks.…”
Section: Discussionmentioning
confidence: 99%
“…The survey employed dichotomised core questionnaires that included a set of optional questions. These questionnaires addressed various aspects related to tobacco use, such as smoking and smokeless tobacco, smoking cessation, exposure to secondhand smoke (SHS), both pro and anti-tobacco media and advertising, access to and availability of tobacco products, as well as knowledge and attitudes regarding tobacco use [ 24 ]. We relied on the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines in preparing this paper.…”
Section: Methodsmentioning
confidence: 99%